Case Report: Successful Treatment of a Child With COVID-19 Reinfection-Induced Fulminant Myocarditis by Cytokine-Adsorbing oXiris® Hemofilter Continuous Veno-Venous Hemofiltration and Extracorporeal Membrane Oxygenation - Phan, Phuc H.; Nguyen, Dung T.; Dao, Nam H.; Nguyen, Ha T. T.; Vu, An V.; Hoang, Son T.; Nguyen, Lam V.; Cao, Tung V.; Tran, Dien M. (Frontiers in Pediatrics, 2022)
Background: Indirect cardiomyocyte damage-related hyperinflammatory response is one of the key mechanisms in Covid-19-induced fulminant myocarditis. In addition to the clinical benefit of using cytokines absorption hemofiltration, the effectiveness of instituting VA-ECMO support for cardiac compromise has been reported. However, current literature enunciates a paucity of available data on the effectiveness of these novel modalities. Case presentation: We reported a 9-year-old boy with recurrent COVID-19 infection causing fulminant myocarditis, who was treated successfully by using novel modalities of oXiris® hemofilter continuous venovenous haemofiltration (CVVH) and veno-arterial extracorporeal membrane oxygenation (VA-ECMO). The patient made a full recovery without any sequelae. Conclusion: We conclude that the novel highly-absorptive hemofilter CVVH and VA-ECMO may be effective treatment modalities in managing SARS-CoV-2-induced fulminant myocarditis. Our report highlights the need for further well-designed investigations to confirm this extrapolation.